Planning and Scheduling AC Product Distribution in PT. XYZ to Fulfill Service Level - Eni, Yuli; Gautama So, Idris; ., Rudi (KnE Social Sciences, 2019)
PT. XYZ has some problems in scheduling ABC product distribution, which the company has excessive stock in the main warehouse, but stockout happened in regional warehouses. Another problem is that the company has established a 90% service level for safety stock, but it is not applied in the regional warehouse. The objectives in this research are to find out the appropriate safety stock quantity so 90% service level that company established can be achieved, to know company distribution schedule, and to count the most efficient expense that company will pay. To aim these research objectives, it started by using the Bayes method to know demand forecasting, then established safety stock quantity to fulfill 90% service level, and using DRP to scheduling company distribution activity. The results from this research are knowing safety stock quantity in the warehouse so it can fulfill 90% service level, knowing distribution schedule, and the most efficient expense that the company has to pay. According to the results, the DRP method can be used to overcome company problems and fulfill their expectation that the company has established, and estimate distribution budget.